UJI ANTIOKSIDAN (E)-1-(4-KLOROFENIL)-3-P-TOLILPROP-2-EN-1-ON DAN (E)-1-(4-KLOROFENIL)-3-(4-ISOPROPILFENIL)PROP-2-EN-1-ON - Eti Meirina Brahmana; Dahlia Dahlia; Rena Lestari; Jismi Mubarak; Ria Karno; Arief Anthonius Purnama (Jurnal Inovasi Pendidikan dan Sains, 2022)
This study aimed to test the antioxidant activity of (E)-1-(4-chlorophenyl)-3-p-tolilprop-2-en-1-on (C1) and (E)-1-(4-chlorophenyl)-3- (4-isopropylphenyl)prop-2-en-1-on (C2). This research is useful as a first step in the search for alternative antioxidant compounds and new antibiotics from chalcone compounds. The antioxidant bioactivity test was carried out using the DPPH method. DPPH is a method that is fast, simple, and does not require high costs in determining antioxidant capacity using the free radical 2,2-diphenyl-1-picrylhydrazil (DPPH). This method is often used to test compounds that act as free radical scavengers or hydrogen donors and evaluate their antioxidant activity, as well as quantify the number of antioxidant-radical complexes formed. The antioxidant bioactivity of chalcone compounds (E)-1-(4-chlorophenyl)-3-p-tolilprop-2-en-1-on has an IC50 value of 533.9000 ppm and chalcone compounds (E)-1-(4-chlorophenyl) -3-(4-isopropylphenyl)prop-2-en-1-on has an IC50 value of 718.9054 ppm. The ability of chalcone compounds (E)-1-(4-chlorophenyl)-3-p-tolylprop-2-en-1-one and (E)-1-(4-chlorophenyl)-3-(4-isopropylphenyl)prop- 2-en-1-on is classified as a weak antioxidant [12]. Keywords : Antioxidant, DPPH, Chalcone